2002
DOI: 10.1021/jp020745m
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in Polyelectrolyte Gels Interacting with Surfactants of Opposite Charge

Abstract: Macroscopic phase separation in covalent sodium polyacrylate (PA) networks following the absorption of cetyltrimethylammonium bromide/chloride (CTAB/C) from aqueous solutions is studied experimentally and theoretically. The gels are shown to consist of a solvent-swollen polyelectrolyte network (core), surrounded by a dense surface phase (skin) of polyion/surfactant complexes. The effect of core swelling on network structure and polyion/surfactant interaction in skins is discussed. It is demonstrated that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
208
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(229 citation statements)
references
References 55 publications
20
208
1
Order By: Relevance
“…This type of behavior will be subsequently referred to as "regular shrinking". These observations have been made earlier by Khandurina et al, 32 working on the reaction of cross-linked polyacrylate gels with alkyltrimethylammonium bromides, and Hansson et al, 34 who also study the interaction of slightly cross-linked sodium polyacrylate (cl-NaPA) with cetyltrimethylammonium bromide (CTAB). Additionally, in this work, we observed that the DNA gels shrink in an irregular fashion when the surfactant concentration is higher than 0.02 mM.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…This type of behavior will be subsequently referred to as "regular shrinking". These observations have been made earlier by Khandurina et al, 32 working on the reaction of cross-linked polyacrylate gels with alkyltrimethylammonium bromides, and Hansson et al, 34 who also study the interaction of slightly cross-linked sodium polyacrylate (cl-NaPA) with cetyltrimethylammonium bromide (CTAB). Additionally, in this work, we observed that the DNA gels shrink in an irregular fashion when the surfactant concentration is higher than 0.02 mM.…”
Section: Resultssupporting
confidence: 56%
“…Previously, values between 110 and 160 were found for CTAB in polyacrylate gels. 34 To the best of our knowledge this is the first evidence of small CTAB micelles in complexes with DNA reported in the literature.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations